Goat-stag, chimera or chameleon? The formation and first semester of the Conte government. Issue 3 (3rd July 2019) - Marangoni, Francesco; Verzichelli, Luca
ABSTRACT: The article deals with the formation and the first semester of activity of the government led by Giuseppe Conte. The genesis of the new 'yellow-green' coalition between the Lega (League) and the Movimento Cinque Stelle (Five-star Movement, M5s) is analysed in the first section, which focuses particularly on the contract stipulated by the two parties in the month of May 2018. The second section deals with the formal process of government formation, while the third analyses the early months of legislative activity of the Conte government. A short concluding section offers an overall assessment of the mid-term evolution of the executive, focussing on its problems of consolidation and discussing some critical prospective issues.